2008
DOI: 10.1097/mbc.0b013e32830b14ef
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of once daily low molecular weight heparin (tinzaparin sodium) in high risk pregnancy

Abstract: Low molecular weight heparin (LMWH) is widely regarded as the anticoagulant treatment of choice for the prevention and treatment of venous thromboembolism during pregnancy. However, previous studies have demonstrated that the pharmacokinetic profiles of LMWH vary significantly with increasing gestation. Consequently, it remains unclear whether LMWH regimens recommended for use in nonpregnant individuals can be safely extrapolated to pregnant women. The aims of this study were to assess the safety and the effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…The very low risk of antepartum major bleeding (0%) found in this study is consistent with that previously reported in the literature, including series reporting twice-daily injections of LMWH during pregnancy [8,20,21,22,26,27,28] and with the bleeding rates reported with the use of LMWH in the non-pregnant population [18,29,30]. …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The very low risk of antepartum major bleeding (0%) found in this study is consistent with that previously reported in the literature, including series reporting twice-daily injections of LMWH during pregnancy [8,20,21,22,26,27,28] and with the bleeding rates reported with the use of LMWH in the non-pregnant population [18,29,30]. …”
Section: Discussionsupporting
confidence: 81%
“…Indeed, except for some recent data from a large multicentre registry [22], only 3 small series reported the use of once-daily therapeutic doses of tinzaparin during 12, 28 and 37 pregnancies respectively [20,21,26]. The large study by Nelson-Piercy et al [22] reported on 1,267 pregnancies treated with tinzaparin at prophylactic (n = 1,013) or therapeutic dosage (n = 254).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During treatment, no systemic venous thrombosis occurred; however, 1 parietal infarct and 1 postpartum CVT were documented. 242 As in nonpregnant women, fibrinolytic therapy is reserved for patients with deterioration despite systemic anticoagulation, and its use has been reported during pregnancy. 243 …”
Section: Cvt During Pregnancymentioning
confidence: 99%